Transcatheter heart valve commissural alignment: an updated review - Akodad, Mariama; Lounes, Youcef; Meier, David; Sanguineti, Francesca; Hovasse, Thomas; Blanke, Philipp; Sathananthan, Janarthanan; Tzimas, Georgios; Leipsic, Jonathon; Wood, David A.; Webb, John; Chevalier, Bernard (Frontiers in Cardiovascular Medicine, 2023)
Transcatheter aortic valve replacement (TAVR) indications recently extended to lower surgical risk patients with longer life expectancy. Commissural alignment (CA) is one of the emerging concepts and is becoming one of the cornerstones of the TAVR procedure in patient with increased longevity. Indeed, CA may improve transcatheter heart valve (THV) hemodynamics, future coronary access and repeatability. The definition of CA has been recently standardized by the ALIGN-TAVR consortium using a 4-tier scale based on CT analysis. Progress has been made during the index TAVR procedure to optimize CA, especially with self-expandable platforms. Indeed, specific delivery catheter orientation, THV rotation and use of computed-tomography derived views have been proposed to achieve a reasonable degree of CA. Recent data demonstrates feasibility, safety and a significant reduction in coronary overlap using these techniques, especially with self-expandable platforms. This review provides an overview of THV CA including assessment methods, alignment techniques during the index TAVR procedure with different THV platforms, clinical impact of commissural misalignment as well as challenging situations for CA.